Awareness and political participation of local rice farmers in Passi City on local government extension programs. - Jamolangue, Mila Mae L.; Torril, Jennifer (2004.)
Awareness and political participation of local rice farmers in Passi City on local government extension programs. c2004. 61 leaves. Undergraduate thesis. B.A. Political Science. U.P. Visayas Abstract : The study sought to determine and describe the structure of relationship between the awareness and political participation of the local rice farmers of Passi City in the implementation of local government extension programs. The study also aims to determine the significance of certain socio-economic characteristics (age, income, number of years in rice farming, educational attainment) to the level awareness and political participation of the respondents. the participants of the study constituted eighty-two (82) local rice farmers coming from Brgy. Pagaypay, Brgy. Sto Tomas and Brgy. Gemat-y., A survey questionnaire was constructed to measure the awareness and political participation of local rice farmers' vis-avis the local government extension programs. The responses were analyzed using Factor Analysis and Canonical Correlation Analysis. A structured interview was also utilized to gather qualitative data from the key informant local rice farmers of the study to supplement the quantitative analysis derived from the responses in the survey questionnaire. The study showed that awareness positively translates into political participation. The study showed that awareness positively translates into political participation. The awareness of local rice farmers to the local government programs holds a higher correlation to their political participation in the implementation of such programs. The awareness of local rice farmers positively translates to political participation as manifested through their initiative of disseminating information regarding the programs. All socio-economic characteristics utilized in the study (age, income, number of years in rice farming, educational attainment) holds significance to the level of awareness of the respondents. However, only educational attainment and income significance holds true in political participation.
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Rice Farmers -- Passi City